Common neuronal mechanisms underlying tics and hyperactivity. (June 2020) - Israelashvili, Michal; Yael, Dorin; Vinner, Esther; Belelovsky, Katya; Bar-Gad, Izhar
Abstract: Tourette syndrome (TS) and attention deficit hyperactivity disorder (ADHD) are two neurodevelopmental hyper-behavioral disorders that are highly comorbid. The source of this comorbidity and the neuronal mechanisms underlying these disorders are still unclear. We examined the neuronal activity of freely behaving rats before and after striatal disinhibition, to reveal the similar and distinct neuronal components underlying the mechanisms of TS-like and ADHD-like symptom expression. Focal disinhibition induced motor tics, locomotor hyperactivity or a comorbid effect depending on the location of the injection within the different functional domains of the striatum. While injections within the motor domain induced motor tics, injections into the limbic domain induced mainly locomotor hyperactivity. Disinhibition, regardless of its striatal location, led to qualitatively similar macro-scale and micro-scale neuronal changes. These changes were localized to the domain of the manipulation and remained partly segregated, indicating that hyperactivity is induced as a result of changes in the limbic domain without directly activating the motor domain. Despite the general similarity of induced neuronal changes, these changes were associated with different behavioral effects and were more stereotypic and pronounced following motor-domain disinhibition in comparison to limbic-domain disinhibition. Our recordings revealed a disparity in the neuronal input–output transformation of the two models of the disorders. The results suggest that tic expression and hyperactivity states share similar local neuronal activity changes which manifest in different neuronal and behavioral outcomes. These results expose an intriguing link between tics and their comorbid symptoms and hint at striatal disinhibition, resulting from GABAergic alterations, as a potential common mechanism underlying distinct symptoms expressed by hyper-behavioral patients.